Особенности государственного регулирования инновационной деятельности предприятий и организаций - Шейко, І. А.; Стороженко, О. В. (НТУ "ХПИ", 2009)
В статті наведені основні підходи до регулювання інноваційної діяльності. Також оцінюється іноваційна активність вітчизняних підприємств, динаміка капіталовкладень за джерелами фінансування, а також структура виробництва за належністю до технологічних укладів. Зроблені висновки щодо причин низької іноваційної активності вітчизнянихпідприємств а такожнапрямах її подолання. In the article the basic approaches to the regulation of innovative activity are described. Innovative activity of domestic enterprises, dynamics of change of capital investments, estimated on sourcings, and also the structure of production after belonging to the technologicalmodes are analyzed. Done conclusions in relation to reasons of low innovative activityof domestic enterprises and also directions of its overcoming.
Keywords: инновационная активность; источники финансирования; капитальные инвестиции; технологический уклад; innovative activity; sources of funding; investment of capital; technological stage